Peran Administrasi Keimigrasian dalam Menjaga Keamanan Nasional: Studi Literatur Tentang Fungsi Pengawasan Orang Asing - Arif Maulana; Arief Febrianto; Hanifa Maulidia (Pusat Riset dan Inovasi Nasional, 2025)
This paper discusses how immigration administration plays a strategic role in maintaining national security, particularly through the function of monitoring the presence and activities of foreign nationals. The study employs a literature review method, referring to legal frameworks, public policy documents, and academic literature concerning data management and foreigner surveillance. The findings indicate that effective oversight relies heavily on an integrated and real-time administrative system, such as the Immigration Management Information System (SIMKIM), Foreigner Reporting Application (APOA), and inter-agency cooperation. This function is not merely administrative but also serves as the frontline for early detection of threats such as transnational crimes, terrorism, and immigration violations. The establishment of the Ministry of Immigration and Correctional Affairs under Presidential Regulation No. 157 of 2024 has further strengthened the institutional structure of foreigner surveillance in Indonesia. This study affirms that strengthening immigration administration is a vital prerequisite for a modern national security system.